MODULATING GLUTEN-TRIGGERED IMMUNITY: THE NEXT STEP IN CELIAC DISEASE TREATMENT - Aleksandra Kubas; Aleksander Sobczyk; Aleksandra Górniak; Michał Widawski; Natalia Gizińska; Paulina Lewandowska; Amelia Rusiecka (World Science, 2025)
Celiac disease (CeD) is an autoimmune condition triggered by gluten ingestion in genetically predisposed individuals. Although a strict gluten-free diet (GFD) remains the gold standard for treatment, many patients experience ongoing symptoms or fail to achieve mucosal healing due to inadvertent gluten exposure and challenges in long-term adherence. These limitations and growing understanding of the pathophysiology of CeD have prompted the development of non-dietary therapies that target the underlying immune mechanisms of CeD. Emerging therapeutic strategies aim to modulate gluten-triggered immunity, including the inhibition of tissue transglutaminase 2 (TG2), blockade of HLA-DQ2.5 and gluten peptide complexes, suppression of interleukin-15 (IL-15), and interference with gut-homing lymphocyte trafficking. Among these, the TG2 inhibitor ZED1227 has demonstrated the most advanced clinical efficacy, while IL-15–targeting agents such as AMG 714 and CALY-002 show promise, particularly in refractory CeD. However, to date, none of those novel immune-modulating strategies have yet demonstrated sufficient efficacy and safety to replace dietary therapy. Therefore, future well-designed, long-term studies are needed to validate the efficacy, safety, and cost-effectiveness of immune-mediated therapies and to define their role in personalized management of CeD.